2022
DOI: 10.1080/21655979.2022.2049959
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut microbiota in patients with benign and malignant brain tumors: a pilot study

Abstract: Gut microbiota is associated with the growth of various tumors, including malignant gliomas, through the brain-gut axis. Moreover, the gut microbiota in patients with malignant tumors may considerably differ from those with benign tumors. However, the associations of gut microbiota with benign and malignant brain tumors remain unclear. Hence, in order to explore these underlying relationships, patients with benign meningioma (n = 32), malignant glioma (n = 27), and healthy individuals (n = 41) were selected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Thus, the existence of the gut-brain axis and the protective effects of the gut flora in both the gut and the brain opens up new possibilities for the development of novel therapeutic techniques for radiation-induced brain injury [48]. Interestingly, it has been noted that patients with brain tumors have a less diverse microbial environment [49]. Further, probiotics have been found to decrease cancer, particularly glioma, which accounts for 81% of all the malignant tumors of the central nervous system and is the most prevalent kind.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the existence of the gut-brain axis and the protective effects of the gut flora in both the gut and the brain opens up new possibilities for the development of novel therapeutic techniques for radiation-induced brain injury [48]. Interestingly, it has been noted that patients with brain tumors have a less diverse microbial environment [49]. Further, probiotics have been found to decrease cancer, particularly glioma, which accounts for 81% of all the malignant tumors of the central nervous system and is the most prevalent kind.…”
Section: Discussionmentioning
confidence: 99%
“…Brain tumor patients have a significantly lower alpha diversity index of intestinal flora compared to healthy controls and a significant dysregulation of intestinal flora structure and function, especially in malignant gliomas. Through statistical analysis, the team identified six abundant genera, namely, Fusobacterium, Akkermansia, Escherichia/Shigella, Lachnospira, Agathobacter, and Bifidobacterium [ 161 ]. This can serve as a foundation for further in-depth studies, and we anticipate early clinical application of these medicines.…”
Section: Impact Of the Local Environmentmentioning
confidence: 99%
“…In addition, it has been reported that gut microbiota could impact on microglial phenotype in brain [ 44 ], with a shift toward a more immune-suppressive and/or tumorigenic condition [ 43 , 44 ]. Furthermore, gut microbiota may be related to the growth of various tumors, suggesting that the identification of gut microbiota could be a tool for the diagnosis of brain tumors [ 45 ] ( Figure 2 ). Through the reduction of cytotoxic NK cells, chronic treatment with antibiotics could stimulate the growth of glioma [ 43 , 46 ].…”
Section: Gut Microbiota May Also Affect the Development Of Gliomamentioning
confidence: 99%
“…Another study has demonstrated that glioma can also induce alterations in the microbiota [ 50 ]. Moreover, a diversity of the gut microbiota with glioma patients has been shown to be different from that of healthy subjects [ 45 , 50 ]. All together, these studies demonstrate that the bidirectional axis between the gut and the brain may be a determinant of the glioma biology.…”
Section: Gut Microbiota May Also Affect the Development Of Gliomamentioning
confidence: 99%